Spent mushroom substrate is capable of physisorption-chemisorption of CO2 - Alves, Lucas da Silva [UNESP]; Moreira, Bruno Rafael de Almeida [UNESP]; Viana, Ronaldo da Silva [UNESP]; Dias, Eustáquio Souza; Rinker, Danny Lee; Pardo-Gimenez, Arturo; Zied, Diego Cunha [UNESP] (Elsevier, 2022)
No in-depth investigation exists on the feasibility of integrating hydrothermal carbonization (HTC) and pelletization into the process of making spent mushroom substrate (SMS), an agro-food residue from the commercial mushroom industry, into an adsorbent for post-combustion CO2 removal. Therefore, this study analyzed if it could be possible for systematically converting low-pressure hydrochars of various SMSs into carbon-adsorbing mini-capsules. Sources of SMS included paddy straw and achiote capsule shell from Pleurotus ostreatus; eucalyptus sawdust and grassy straw from Lentinula edodes; and compost containing peat or soil as casing layer from Agaricus subrufescens. The eucalyptus sawdust and grassy straw from L. edodes outperformed the other biomaterials in adsorbing CO2, and thus effectively encapsuled most of the gas, 8.25 mmol g−1 and 8.10 mmol g−1, respectively. They contained mostly hetero-atoms of O and N, requiring less unit energy to bind acidic molecules of CO2 at the alkaline sites. The amount of unit energy the pore-filling process demanded at 25 °C was 12.65 kJ mol−1, an attribute of self-sustaining and saleable physisorption. A negative 6.80 kJ mol−1 free energy validated both spontaneity and exothermal of biocarbons at steady-state atmosphere. The major findings and innovations of our study support utilizing SMS as an adsorbent as a carbon capture, storage and utilization networking. Our insights into the physisorption-chemisorption on SMS are timely and relevant to help manage the re-use of SMS, and thus bring the global mushroom industry closer to environmental sustainability and toward a lower carbon society and circular economy.
Keywords: Agro-food residue; Hydrothermal carbonization; Microporous carbonaceous material; Pelletization; Physical sorbent; Post-combustion greenhouse gas